PEMANFAATAN METODE IMPRESIF TERHADAP PROSES PENGEMBANGAN KARAKTER SISWA - Karim, Ahmad Abdul; Firdaus, Muhamad Yuda; Dewi, Rizky Kurnia; Yuliani, Yuliani; Hartati, Dian (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2021)
Teaching literature during a pandemic can be an alternative in developing character in students. This research is important to do to see the convergence of performances that are usually watched once, but due to digitalization, it is now easier for viewers to enjoy the performance. This study reveals the role and function of virtual drama staging in character building in children during the pandemic. The research data source is the recording of the virtual performance of Theater Comma entitled "Pandemi" by N. Riantiarno. The approach used is descriptive qualitative. And the method used is descriptive qualitative method. This study uses an objective (approachstructural).The findings found several values of character strengthening, namely religious, honest, responsible, and social care. These four values can be seen from the dialogue between actors to the attitude of the actors in responding to the pandemic. Based on the values of character education found, it shows that virtual performances are able to become a relevant literary medium for planting character education in the distance learning period. Keywords: Teaching Literature, Virtual Performances, Character Education, Structural, Theater Comma